The Transversal Competence of Using ICTs in Students of Archival Studies - Maureen Rebeca Herrera-Brenes; Idalí Calderón-Salas; Jaime Ricardo Valenzuela-González (Revista Electronic@ Educare, 2015)
The main purpose of this research is “to describe the characteristics that distinguish expert apprentices at the competence of using ICTs among students of Archival Studies.” The methodology was based on mix methods research and the main theory used was the theory of beginners and experts. The research was developed at the Archival Studies Section of the School of History at the Universidad of Costa Rica. The study was developed with students 18 to 28 years old. There were two phases, qualitative and quantitative. After analyzing the data collected, the research questions were answered. Results include a list of characteristics of expert apprentices at using ICTs and recommendations about how to encourage this skill. Experts apprentices in ICTs use a number of characteristics: autonomy and creativity to solve challenges related to the use of ICTs for self-learning, tendency to satisfy curiosity, willingness to seek solutions to the technological challenges associated with the everyday life, interest in developing a better performance than their peers in the use of technological tools, incorporating technology to personal life, critical attitude about information, and permanent interest in learning.